(untitled) (Isagoge - Journal of Humanities and Social Sciences, 2021)
Universal Design for Learning stands at the forefront of educational policy to create universal access to educational curricula for all students, including students with special needs. The ColorADD system is a universal language, describing the three main colors, blue, yellow and red with simple graphic symbols, which, through coding and addition combinations, can associate and record the entire color palette. The ColorADD recognition system developed by Dr. Miguel Neiva. Τhe application of a color code alphabet in very essential. It can be used in many sectors, such as music education, and will concern education and educational integration policy, but also the global community with various applications for various aspects of human activities.